Pharmacokinetic Studies of New Stimulator of Brain Cognitive Functions OSPL-502 - Pukhov, S.A.; Grigoriev, V.V.; Kozlovskiy, V.I.; Romanova, A.A.; Shishko, G.D.; Neganova, M.E.; Klochkov, S.G. (Biomedical Chemistry: Research and Methods, 2018)
The main pharmacokinetic parameters of a new stimulator of cognitive brain functions, OSPL – 502 have been determined: area under the concentration-time curve, elimination rate constant, half-elimination period, time to reach the maximum concentration, maximum concentration, volume distribution, total clearance and bioavailability of the dosage form. The main metabolites of the active substance of the dosage form of the new stimulator of cognitive functions OSPL – 502 have been analyzed. The data obtained predict the effects of the drug in humans relevant for further clinical investigation.